2013
DOI: 10.1371/journal.pgen.1003532
|View full text |Cite
|
Sign up to set email alerts
|

GLIS3, a Susceptibility Gene for Type 1 and Type 2 Diabetes, Modulates Pancreatic Beta Cell Apoptosis via Regulation of a Splice Variant of the BH3-Only Protein Bim

Abstract: Mutations in human Gli-similar (GLIS) 3 protein cause neonatal diabetes. The GLIS3 gene region has also been identified as a susceptibility risk locus for both type 1 and type 2 diabetes. GLIS3 plays a role in the generation of pancreatic beta cells and in insulin gene expression, but there is no information on the role of this gene on beta cell viability and/or susceptibility to immune- and metabolic-induced stress. GLIS3 knockdown (KD) in INS-1E cells, primary FACS-purified rat beta cells, and human islet ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
159
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(166 citation statements)
references
References 74 publications
(119 reference statements)
5
159
1
Order By: Relevance
“…The expressions of Bim, c-Myc, and DP5 are induced by cytokines in β-cells, and Bim and DP5 are regulated, at least in part, through JNK (25)(26)(27). Importantly, knockdown of DP5 or Bim significantly decreases cytokine-induced apoptosis in both human and rodent β-cells (26)(27)(28), and the proapoptotic effects of Bim in β-cells are modulated by two other candidate genes for T1D, namely PTPN2 (26) and GLIS3 (28). These observations suggest that CTSH protects against β-cell apoptosis through inhibition of JNK and p38 signaling and consequent activation of key proapoptotic genes.…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of Bim, c-Myc, and DP5 are induced by cytokines in β-cells, and Bim and DP5 are regulated, at least in part, through JNK (25)(26)(27). Importantly, knockdown of DP5 or Bim significantly decreases cytokine-induced apoptosis in both human and rodent β-cells (26)(27)(28), and the proapoptotic effects of Bim in β-cells are modulated by two other candidate genes for T1D, namely PTPN2 (26) and GLIS3 (28). These observations suggest that CTSH protects against β-cell apoptosis through inhibition of JNK and p38 signaling and consequent activation of key proapoptotic genes.…”
Section: Discussionmentioning
confidence: 99%
“…The rat insulin-producing INS-1E cell line, kindly provided by C. Wollheim (University of Geneva, Switzerland) [25], was maintained in RPMI 1640 GlutaMAX-I medium (Invitrogen) [26].…”
Section: Methodsmentioning
confidence: 99%
“…An in vitro study showed that Glis3 knockdown in INS-1 cells increased basal and inflammatory cytokine (IL1β + IFNγ)-or palmitate-induced β cell apoptosis. Reduced GLIS3 expression was found to modulate the alternative splicing of the pro-apoptotic BH3-only protein Bim, promoting the expression of the pro-death variant BimS and β cell death (Nogueira et al 2013). These data suggest that proper GLIS3 expression could be required for β cell survival.…”
Section: Glis3 May Protect Pancreatic β Cells Against Apoptosismentioning
confidence: 80%
“…2). GLIS3 potently controls insulin gene transcription , ZeRuth et al 2013 as well as likely insulin secretion (Kang et al 2009b and β cell survival (Nogueira et al 2013, Dooley et al 2016, which perturbations may underlie all three forms of diabetes. Mutations or deletions in GLIS3 impair the proper expression and/or function of GLIS3 and its direct downstream target NGN3, causing severely abnormal β cell development in utero and marked impairment in insulin production at birth, culminating in permanent neonatal diabetes .…”
Section: Discussionmentioning
confidence: 99%